2023
DOI: 10.1177/10755470231184203
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Skeptical About Scientific Innovation? Examining Worldview Predictors of Artificial Intelligence, Nanotechnology, and Human Gene Editing Attitudes

Abstract: This work examines worldview predictors of attitudes toward nanotechnology, human gene editing (HGE), and artificial intelligence. By simultaneously assessing the relative predictive value of various worldview variables in two Dutch samples (total N = 614), we obtained evidence for spirituality as a key predictor of skepticism across domains. Religiosity consistently predicted HGE skepticism only. Lower faith in science contributed to these relationships. Aversion to tampering with nature predicted skepticism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…When posting The SmartMiner concept, we had in mind an observation published in (Crawford & Calo, 2016;Janković et al, 2021;Većkalov et al, 2023;Bozkurt & Gursoy, 2023;Yampolskiy, 2024) in sense that "Machines and robots that outperform humans across the board could self-improve beyond our controland their interests might not align with ours". Broad popular and scientific discourses concern massive use of Artificial Intelligence and Machine Learning appeared.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…When posting The SmartMiner concept, we had in mind an observation published in (Crawford & Calo, 2016;Janković et al, 2021;Većkalov et al, 2023;Bozkurt & Gursoy, 2023;Yampolskiy, 2024) in sense that "Machines and robots that outperform humans across the board could self-improve beyond our controland their interests might not align with ours". Broad popular and scientific discourses concern massive use of Artificial Intelligence and Machine Learning appeared.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous research has shown that various forms of anti-science attitudes correlate with diverse ideologies (e.g., Pechar et al, 2018;Rutjens et al, 2018bRutjens et al, , 2022Washburn and Skitka, 2018;Rutjens and van der Lee, 2020;Schrøder, 2022). However, overarching anti-science attitudes tend to mediate the effect of different ideological variables when predicting anti-science attitudes across domains (Rutjens et al, 2018a(Rutjens et al, , 2022Rutjens and van der Lee, 2020;Većkalov et al, 2023).…”
Section: Introductionmentioning
confidence: 98%